2009
DOI: 10.5194/angeo-27-487-2009
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving mesospheric water vapour from observations of volume scattering radiances

Abstract: Abstract. This study examines the possibility for a theoretical approach in the estimation of water vapour mixing ratios in the vicinity of polar mesospheric clouds (PMC) using satellite observations of Volume Scattering Radiances (VSR) obtained at the wavelength of 553 nm. The PMC scattering properties perturb the underlying molecular Rayleigh scattered solar radiance of the background atmosphere. As a result, the presence of PMC leads to an enhancement in the observed VSR at the altitude of the layer; the PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“… Vergados and Shepherd [2009] employed the CARMA (Community Aerosol and Radiation Model for Atmospheres) model to predict PMC scattering from the ice crystals simulated by the model. These were compared with the WINDII PMC observations and the water vapor profiles adjusted to match the model results with the observations.…”
Section: Windii Spin‐off Science: Airglow No O+ Pmc and Solar Flaresmentioning
confidence: 99%
See 1 more Smart Citation
“… Vergados and Shepherd [2009] employed the CARMA (Community Aerosol and Radiation Model for Atmospheres) model to predict PMC scattering from the ice crystals simulated by the model. These were compared with the WINDII PMC observations and the water vapor profiles adjusted to match the model results with the observations.…”
Section: Windii Spin‐off Science: Airglow No O+ Pmc and Solar Flaresmentioning
confidence: 99%
“…Richmond et al [2003],Shepherd [2011],Thuillier et al [2002] Polar mesospheric clouds were observed in an imaging mode but also in normal operations. et al[1995],Shettle et al [2002],Vergados and Shepherd [2009], Wiens et al[1995] Auroral emission rate profiles were observed both in the daytime and at night, allowing auroral excitation and the influence of geomagnetic disturbances to be studied.…”
mentioning
confidence: 99%
“…This is because there is more than one solution when fitting the observed signal to the simulated T-matrix spectra for large particles and scattering angles > 90 • (see von Savigny et al, 2005, Fig. 3 for an equivalent issue).…”
Section: Osiris Retrievalmentioning
confidence: 99%
“…It has been used to simulate NLCs in numerous publications (e.g. Asmus et al, 2015;Kiliani et al, 2015;Chandran et al, 2012;Megner, 2011;Megner et al, 2006;Rapp and Thomas, 2006;Merkel et al, 2009;Stevens, 2005;Vergados and Shepherd, 2009;Lübken et al, 2007). As in the majority of these studies, we use the 1-dimensional set-up of the model to simulate microphysical processes such as ice nucleation and growth, sedimentation and vertical transport.…”
Section: Carma Modelmentioning
confidence: 99%
“…It has been used to simulate NLCs in numerous publications (e.g. Asmus et al, 2015;Kiliani et al, 2015;Chandran et al, 2012;Megner, 2011;Megner et al, 2006;Rapp and Thomas, 2006;Merkel et al, 2009;Stevens, 2005;Vergados and Shepherd, 2009;Lübken et al, 2007). As in the majority of these studies, we use the 1-dimensional set-up of the model to simulate microphysical processes such as ice nucleation and growth, sedimentation and vertical transport.…”
Section: Carma Modelmentioning
confidence: 99%